Prevalence and Molecular Characterization of TEM and CTX-M Beta-Lactamase Genes of Escherichia coli Isolated From Cow Milk - Aly, Amr M.; Bahamdain, Lina Ahmed; El-kholy, Aziza S.; Alsebaey, Ehab F.; M. Aly, Magda; El-Halmouch, Yasser H. (Journal of Contemporary Medical Sciences, 2024)
Objective: The study objective was to investigate the presence and antibiotic resistance of toxigenic E. coli strains in the raw milk of dairy cattle and to determine the prevalence of blaTEM and blaCTX-M genes in the selected isolates. Methods: Two hundred raw milk samples were collected from 20 dairy farms located in Kafr El Sheikh City. Results: Among the samples, 60 were positive for E. coli. The sensitivity of these isolates was detected against different antibiotics. Using the disk diffusion test, all the isolates were resistant to at least two beta-lactam antibiotics. The resistance to beta-lactam antibiotics by the selected E. coli was varied to be highly significant. Five percent of the tested E. coli was highly resistant with a multi-antibiotic resistant (MAR) index, of 1.0, while 8% had the lowest MAR (0.14). Both blaTEM and blaCTX-M resistant genes were detected in isolate No. 52, while, blaCTX-M was detected in isolate No. 34 and blaTEM was detected in isolates No. 9, 21, 28, and 40. The PCR products of blaTEM and blaCTX-M genes were sequenced and deposited in the GenBank of the NCBI database with the accession numbers OR450046 and OR879117, respectively. Conclusion: The macrolides group of antibiotics especially erythromycin should not be a suitable treatment of dairy herds for mastitis by E. coli in Egypt. The majority of E. coli was multiple-antibiotic resistant and co-carried many virulence genes, and it may pose a great potential risk to public health.